So bright a darkness - Iweka, Chidubem (Fiction (Ibadan, Nigeria), 2014)
Okafor ran wildly through the jungle, the phantom captain and his ghoulish platoon in hot pursuit. The faster he ran the more they gained on him. The earth suddenly became marshy and slippery under his feet, impeding speed and balance. He came to an intersection where the jungle paths crossed and saw a mound of earth about four feet high. Just beyond the mound stood a giant Iroko tree. Intuitively, he knew that if he jumped over the mound and quickly climbed up the tree, the ghostly captain and his soldiers would lose him. Eons merge in interstellar whirls. Realism, science fiction and fantasy fuse to drive this drama of transition, cross civilisation and self-discovery.